Penerapan Internet of Things untuk Penyiraman dan Pemupukan Tanaman Selada Merah Pada Metode Tanam Vertikultur menggunakan Bot Telegram - Wijayanto, Ardhi; Amalia Santy Yohara, Silvya; Aziz, Abdul (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2023)
Indonesia as an agricultural country with the majority of the population as farmers, faces the challenge of narrowing land due to the times with building construction and land clearing. In an effort to overcome this narrow area, the Verticulture method was used, where planting was carried out in stages or vertically. This method is suitable for growing vegetables, medicinal plants and ornamental plants, including red lettuce which has high economic value and is rich in nutrition. However, routine plant maintenance, such as watering and fertilizing, is often forgotten due to the busyness of plant owners. To overcome this problem, IoT technology is used with the Wemos D1 R2 Board as a substitute for Arduino, YL-69 sensors, water pumps, and Telegram Bots as a liaison with users. Testing of the IoT prototype system shows the success of the YL-69 sensor in reading soil moisture data and detecting the state of the planting medium. Water pumps and fertilizer pumps can function according to a predetermined humidity value and time. The water pump is successfully started according to the predetermined soil moisture value, which is more than 13000 and successfully turns off when the soil moisture value is less than 11500. The fertilizer pump is also successfully started according to the time determined using the RTC DS3231, namely on Wednesday at 08.00 and turns off after 1 minute.